1991
DOI: 10.1021/bi00241a015
|View full text |Cite
|
Sign up to set email alerts
|

Nonreductive interaction of vanadate with an enzyme containing a thiol group in the active site: glycerol-3-phosphate dehydrogenase

Abstract: The inhibitory effects of vanadium(V) were determined on the oxidation of glycerol 3-phosphate (G3P) catalyzed by glycerol-3-phosphate dehydrogenase (G3PDH), an enzyme with a thiol group in the active site. G3PDH from rabbit muscle was inhibited by vanadate, and the active inhibiting species were found to be the vanadate dimer and/or tetramer. The dimer was a sufficiently weak inhibitor at pH 7.4 with respect to G3P; the tetramer could account for all the observed inhibition. The tetramer was a competitive inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…This and other studies illustrate how useful 51 V NMR spectroscopy is to determine the vanadate species responsible for the interactions with a particular protein or form of a protein [1,30,32,45,84]. For instance, with the SR Ca 2+ -ATPase, it was suggested that monomeric vanadate inhibits the enzyme activity [94] and the vanadate oligomers interact particularly with the E2 conformation of the enzyme [97].…”
Section: Decavanadate Interactions and Effects In Proteinsmentioning
confidence: 95%
See 1 more Smart Citation
“…This and other studies illustrate how useful 51 V NMR spectroscopy is to determine the vanadate species responsible for the interactions with a particular protein or form of a protein [1,30,32,45,84]. For instance, with the SR Ca 2+ -ATPase, it was suggested that monomeric vanadate inhibits the enzyme activity [94] and the vanadate oligomers interact particularly with the E2 conformation of the enzyme [97].…”
Section: Decavanadate Interactions and Effects In Proteinsmentioning
confidence: 95%
“…1) is a more potent inhibitor than the vanadate (V 1 ) was reported for 6-phosphogluconate dehydrogenase [63] almost two decades ago. This investigation was followed up with a study of glucose-6-phosphate dehydrogenase [81] and a number of other enzymes [4,[82][83][84][85][86]. Since then many observations have followed, documenting the specific interactions between various proteins and different oxovanadate anions [4,27,45].…”
Section: Decavanadate Interactions and Effects In Proteinsmentioning
confidence: 99%
“…mild competitive inhibition of glucose-6-phosphate dehydrogenase [472] [473] and 1,6-bisphosphate fructose aldolase from rabbit muscle [474] and a non-competitive inhibitor of rabbit muscle glycerol-3-phosphate dehydrogenase [475].…”
Section: Lysozymementioning
confidence: 99%
“…These and other studies indicated that the mode of action of V varied with the agent employed. Both animal (Crans et al, 2004;Buglyo et al, 2005;Thompson et al, 2006) and in vitro studies (Crans et al, 1990(Crans et al, , 1996Crans and Simone, 1991) noted differential effects from V agents with varying forms, redox states, or coordinated ligands.…”
Section: Introductionmentioning
confidence: 99%